The effect of sleep apnea severity on cardiac autonomic activity during night time in obstructive sleep apnea patients - Ozkececi, Gulay (2016)
CONTEXT AND OBJECTIVE: Impaired autonomic cardiac function is an important consequence of obstructive sleep apnea (OSA). This impairment is mainly due to intermittent hypoxia episodes following apneas. However, the impact of apnea severity on autonomic cardiac function remains unclear. The aim of this study was to evaluate the relationship between the severity of sleep apnea and heart rate turbulence (HRT) and heart rate variability (HRV) in OSA. DESIGN AND SETTING: Observational cross-sectional study conducted in the Departments of Cardiology and Pulmonary Diseases, Afyon Kocatepe University, Turkey. METHODS: 106 patients with OSA and 27 healthy volunteers were enrolled. Based on apnea hypopnea index (AHI) values, obstructive sleep apnea severity was classified as follows: mild OSA (AHI ≥ 5 and < 15), moderate OSA (AHI ≥ 15 and ≤ 30) and severe OSA (AHI > 30). HRV and HRT parameters were assessed via 24-hour digital Holter electrocardiogram recordings for all subjects. RESULTS: HRV and HRT results were significantly lower among OSA patients than among control subjects (P < 0.05). However, there were no significant differences in HRT and HRV between the three patient subgroups. Correlations did emerge between AHI and the NN-interval parameter RMSSD and between oxygen desaturation and turbulence slope (respectively: r = -0.22, P = 0.037; and r = -0.28, P = 0.025). CONCLUSION: HRT and HRV results deteriorate in OSA. Correlations between apnea severity and these parameters seem to be present.